Biotransformation of alkylbenzenes and alkylcylcophexanes by genetically engineered Yarrowia lipolytica strains - Ramorobi, Limpho Martha (University of the Free State, 2008)
Y. lipolytica has the ability to utilise hydrophobic hydrocarbons as carbon sources. It is also an attractive host for heterologous expression of cytochrome P450 (CYP) genes. Y. lipolytica strains with CYP genes cloned under control of two different promoters, pPOX2 and pICL were used in this study. The purpose of this project was to detect the effect of cloned alkane hydroxylases in Y. lipolytica. Alkylbenzenes and alkylcyclohexanes were used to compare the hydroxylase activities of the genetically engineered strains with control strains. Butylbenzene and hexylbenzene were transformed to phenylacetic acid while pentylbenzene, heptylbenene and nonylbenzene yielded benzoic acid as product. Butylcyclohexane and limonene were transformed to cyclohexylacetic acid and perillic acid, respectively, as major products. The activity towards hexylbenzene was highest. Phenylhexanoic acid and phenylbutanoic acid were also for the first time observed as intermediates in the biotransformation of hexylbenzene. Y. lipolytica strains expressing alkane hydroxylases under pPOX2 were induced with oleic acid and harvested. A strain with multiple copies of a proven alkane hydroxylase, cloned, had in one experiment higher activity than the other strains, towards both hexylbenzene and nonylbenzene. However, these results could not be confirmed, because in subsequent experiments the resting cells had very low activities. Ethanol and sodium acetate were used as inducers in the experiments conducted with Y. lipolytica strains with CYP557A1, a putative alkane and/or fatty acid hydroxylase, cloned under pICL. The substrates were added directly to the cells. With single addition of ethanol, the strain with cloned CYP557A1 had in one whole cell experiment with butylbenzene as substrate higher activity than the control strains. With multiple additions of sodium acetate the strain with cloned CYP557A1 showed higher activity in two shake flask experiments when hexylbenzene was used as a substrate. However, when ethanol and sodium acetate were used as inducers the alkylbenzenes were often consumed without the equivalent formation of detectable products, complicating the interpretation of results. This also happened in bioreactor experiments. Biotransformation of alkylcyclohexanes also did not demonstrate the effect of the cloned gene, since the activities of the test strain with CYP557A1 cloned under pICL and the control strain were similar. Alkylcyclohexanes are not promising substrates to distinguish between hydroxylase activity of the cloned genes as they are very volatile and activity towards them is relatively low.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2008
Keywords: Yeast fungi -- Biotechnology; Hydrocarbons -- Biodegradation; Biotransformation (Metabolism); Organic compounds -- Biodegradation; CYP; CPR; Cytochrome P450 monooxygenase; Hydroxylase activity; ICL promotor; Phenylacetic acid; POX2 promoter; Yarrowia lipolytica; Benzoic acid; Alkylcyclohexanes; Alkylbenzenes